Transforming maternal health through continuous midwifery care success in Indonesia: Mengubah kesehatan ibu melalui keberhasilan asuhan kebidanan yang berkesinambungan di Indonesia - Azizah, Siti Nur; Rosyidah, Rafhani (Universitas Muhammadiyah Sidoarjo, 2024)
This case study evaluates Continuity of Care (CoC) in midwifery for a 28-year-old multiparous woman at Wonoayu Community Health Center, Sidoarjo. Over one month, from late pregnancy through postpartum and family planning, comprehensive care was provided. The study found that CoC facilitated early problem identification and treatment, resulting in a normal delivery and effective postpartum and neonatal care. The continuous support enhanced maternal comfort and family satisfaction, highlighting CoC's potential to improve maternal and neonatal health outcomes in community settings.